Pengaruh Pengaruh Model Pembelajaran Kooperatif Tipe Jigsaw Terhadap Kemampuan Penalaran Matematis Peserta Didik Pada Materi Sistem Persamaan Linear Dua Variabel Kelas VIII SMP Swasta Cerdas Bangsa T.A. 2022/2023 - Tri Windi Yanti (Prodi Pendidikan Matematika FKIP Universitas HKBP Nommensen, 2022)
This study aims to determine the effect of the jigsaw cooperative learning model on students' mathematical reasoning abilities on the material of a two-variable linear equation system for class VIII SMP Swasta Cerdas Bangsa T.A. 2022/2023. The research approach used is quantitative, the type of research is Quasi Experiment. The research population was all students of class VIII SMP Swasta Cerdas Bangsa. By using the Cluster Random Sampling technique, the research sample was obtained as an experimental class (VIII-C) and as a control class (VIII-A). The instruments used are tests and observations. So based on the results of the calculation on the connection capability, it shows that the value (sig.) is at the 5% significance level. Based on the calculation of the experimental class on the mathematical reasoning ability of students, the average value is = 85.60. In the control class, the students' mathematical reasoning ability has an average value of = 73.80. By paying attention to the value (sig.) obtained, it can be concluded that there is a significant effect of the jigsaw type cooperative learning model on students' mathematical reasoning abilities on the material of a two-variable linear equation system for class VIII SMP Swasta Cerdas Bangsa T.A. 2022/2023. Based on the average value of the ability between classes, it can be concluded that the jigsaw cooperative learning model has a higher influence than conventional learning models on students' mathematical reasoning abilities on the material of a two-variable linear equation system for class VIII SMP Swasta Cerdas Bangsa T.A. 2022/2023. Keywords: Jigsaw Cooperative Type, Mathematical Reasoning Ability